The Effect of Using Busy Box Creative Little Scientists on Critical Thinking Skills of 5-6 Year Old Children - Alipiyani, Siti; Mirawati, Mirawati; AM, Muh Asriadi; Silawati, Endah (Jurnal Pendidikan Progresif, 2024)
The Effect of Using Busy Box Creative Little Scientists on Critical Thinking Skills of 5-6 Year Old Children. Objectives: This study aims to determine the effect of using the Busy Box Creative Little Scientists learning media in the learning process on the critical thinking skills of children aged 5-6 years. Methods: This quasi-experimental study involved 21 students aged 5-6 years, divided into two classes: a control class and an experimental class. Students were selected by purposive sampling. The experimental class used the Busy Box Creative Little Scientists learning media, while the control class did not. Critical thinking skills were measured before and after the intervention, and the N Gain was calculated to compare the improvement. Findings: The results showed a significant difference in the critical thinking skills of children between the experimental and control classes. The experimental class showed an N Gain of 64%, while the control class had an N Gain of 44%. Conclusion: The study highlights the effectiveness of Busy Box Creative Little Scientists in improving the critical thinking skills of children aged 5-6 years. These findings support further exploration into the use of interactive learning media for enhancing critical thinking in early childhood education. Keywords: learning media, critical thinking skills, early childhood.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024110